Influence of the serotonin transporter 5HTTLPR polymorphism on symptom severity in irritable bowel syndrome. - Rocchina Colucci; Dario Gambaccini; Narcisa Ghisu; Giuseppe Rossi; Francesco Costa; Marco Tuccori; Nicola De Bortoli; Matteo Fornai; Luca Antonioli; Angelo Ricchiuti; Maria Gloria Mumolo; Santino Marchi; et al. (PLoS ONE, 2013)
5HTTLPR polymorphism of serotonin transporter yields short (S) and long (L) alleles. SS and LS genotypes are associated with reduced expression of serotonin transporter. This cross-sectional study investigated the association of 5HTTLPR with symptom severity of irritable bowel syndrome (IBS). Patients with IBS (Rome III) and healthy controls were included. Genomic DNA was extracted from saliva, and 5HTTLPR alleles were assessed by polymerase chain reaction. IBS symptom severity was evaluated by means of IBS-SSS questionnaire. Two hundreds and four IBS patients (159 females; mean age: 39.6±12.3 years; 106 with constipation: C-IBS; 98 with diarrhea: D-IBS) and 200 healthy controls (154 females; mean age: 40.4±15.8 years) were enrolled. The overall IBS-SSS value was higher in LS/SS than LL patients (319.0±71.5 versus 283.8±62.3; P = 0.0006). LS/SS patients had also higher values of abdominal pain (59.7±21.0 versus 51.0±18.8; P = 0.020) and bowel dissatisfaction (80.1±23.9 versus 70.5±22.8; P = 0.035). The overall IBS-SSS values in C-IBS and D-IBS patients were 317.2±68.3 and 296.1±71.4, respectively (P = 0.192), with significantly higher values for abdominal distension (65.0±24.4 versus 51.4±24.8; P = 0.0006), but not for bowel dissatisfaction (80.5±21.7 versus 72.9±25.7; P = 0.138). Frequencies of 5HTTLPR genotypes did not differ significantly when comparing IBS patients (overall or upon stratification in C-IBS and D-IBS) with healthy controls. In conclusion, the LS and SS genotypes are significantly correlated with IBS symptom severity, although their possible direct causal role remains to be proven. In addition, the present findings do not support an association of 5HTTLPR with IBS or its clinical presentation in terms of bowel habit predominance.